2016
DOI: 10.1111/opn.12122
|View full text |Cite
|
Sign up to set email alerts
|

Caring for HIV‐positive orphans in the context of HIV and AIDS: perspectives of Botswana grandmothers

Abstract: Nurses working with older people caring for HIV positive orphans need to develop culturally sensitive HIV education programs that address needs specific to.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…A number of studies in South Africa have commented on the importance of the extended family and caregivers other than parents (23,24,26,27,28). In addition, this study supported ndings in other research (17,22) for the need for healthcare providers and programs to recognise that there are differences in SRH communication and conversations between parents and grandparents. Aubel (2005) showed that the concern that grandmothers might be biased and unable to adapt to new ideas was incorrect and that this should not be a reason that interventions do not make use of older people as drivers in community and family-based interventions (29).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…A number of studies in South Africa have commented on the importance of the extended family and caregivers other than parents (23,24,26,27,28). In addition, this study supported ndings in other research (17,22) for the need for healthcare providers and programs to recognise that there are differences in SRH communication and conversations between parents and grandparents. Aubel (2005) showed that the concern that grandmothers might be biased and unable to adapt to new ideas was incorrect and that this should not be a reason that interventions do not make use of older people as drivers in community and family-based interventions (29).…”
Section: Discussionsupporting
confidence: 77%
“…In addition, this study found that the age and frailty of grandparents as caregivers makes older caregivers' experiences unique (13).Generational differences present their own speci c challenges for example, child discipline and disharmony in the family in intergenerational relationships (13). As a result, grandparents may not feel prepared to conduct SRH conversations which is and di culties are exacerbated by the lack of resources to assist and prepare grandparents for SRH conversations (15,22).…”
Section: Grandparents Wanted To Have Open Srh Conversations About Sexmentioning
confidence: 92%
See 2 more Smart Citations
“…The change of roles is likely to affect the older caregivers’ quality of life (QOL), particularly when they are income insecure. Literature is replete with burdens of HIV and AIDS and income insecurity across many sub-Saharan African countries including Zimbabwe ( Aboderin & Beard, 2014 ; Aransiola, Akinyemi, Akinlo, & Togonu-Bickesteeth, 2017 ; Hondras et al, 2015 ; Mhaka-Mutepfa, Cumming, & Mpofu, 2014 ; Mhaka-Mutepfa, Hunter, Mpofu, & Cumming, 2016 ; Shaibu, 2016 ). Income insecurity also affects the children in the aging adult’s care because 50% to 60% of orphans live with grandparents ( Murray et al, 2012 ; United Nations Programme on HIV and AIDS [ UNAIDS], 2015 ) in sub-Saharan African settings.…”
Section: Introductionmentioning
confidence: 99%